Pelatihan Pengolahan Limbah Tongkol Jagung Menjadi Kerupuk Sebagai Peluang Usaha di Kenagarian Aie Tajun Lubuk Alung - Senjawati, Maria Isfus; Maryam, Maryam; Alfi, Rizki; Syahmer , Verra (Journal of Industrial Community Empowerment, 2022)
This time, corn cob waste has not yet been utilized optimally, while corn cob waste is rich in pentoses and has great potential to be processed into food. There is a business opportunity for the community to process corn cob waste into crackers, in order to generate added value in addition to selling shelled corn. The problem of processing corn cob waste by the community and how to take advantage of this business opportunity can be overcome by providing processing technology and assistance in processing corn cob waste into crackers to the community. Because of this, it is necessary to increase business opportunities by taking advantage of the potential of corn cob waste to become products that can be used as additional products such as processed food products, corn cob crackers through a short training in Nagari Aie Tajun, Lubuk Alung. The evaluation results from this exercise show that the participants are very satisfied and can make this product independently so that they are encouraged to develop this product into a superior product in their hometown.